The use of phages for the removal of infectious biofilms - Azeredo, Joana (2008)
Biofilm formation occurs spontaneously on both inert and living systems and is an important bacterial survival strategy. In humans bioflms are responsible for many pathologies, most of them associated with the use of medical devices. A major problem of biofilms is their inherent tolerance to host defences and antibiotic therapies; there is therefore an urgent need to develop alternative ways to prevent and control biofilm-associated clinical infections. Several in vitro experiments have shown that phages are able to infect biofilm cells and that those phages inducing the production of depolymerases have an advantage since they can penetrate the inner layers of the biofilm by degrading components of the biofilm exopolymeric matrix. In practice clinically relevant biofilms and especially those associated with the use of medical devices can possibly be controlled for example by the topic application or the impregnation of the surface of the device with a phage solution. Another interesting approach has been the use of a phage encoding a phage polysaccharide lyase to treat Pseudomonas aeruginosa biofilms in cystic fibrosis patients by aerosol administration. All these strategies require prior identification of the phage and/or polysaccharide depolymerase capable of infecting the bacterial cells and degrading the polysaccharide within the biofilm, respectively. The biofilm organisms must therefore be isolated and screened against a bank of phages. This procedure is essential and raises important biotechnological challenges: the existence of a bank of phages well characterised (physiologically and genetically) whose efficacy in vivo has been tested and pharmacokinetics studied; the existence of economical and safe production protocols and purification methods (e.g. the presence of endotoxins in a phage preparation may compromise phage therapy). It is however important to consider the fact that the chances of getting a specific phage with a high lytic capability and preferential expressing a relevant exopolymer degrading enzyme is likely to be low. Genetically engineered phages can play an important role in this process. Phages can be genetically manipulated to alter their host range and to induce the production of depolymerases. It is therefore important to reinforce the application of synthetic biology to engineer phages able to efficiently degrade medical biofilms. It is also important to develop efficient methods of phage delivery and to study “in vivo” the phage performance against biofilms. It is still not clear how effective the biofilm can be in protecting the phages against the immune system. Efficient and economic phage production and purification protocols need also to be addressed before one can hope to use phage treatment to prevent or control infectious biofilms.